If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 50 = 5x + 2x + 10 Reorder the terms: 50 + 3x = 5x + 2x + 10 Reorder the terms: 50 + 3x = 10 + 5x + 2x Combine like terms: 5x + 2x = 7x 50 + 3x = 10 + 7x Solving 50 + 3x = 10 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 50 + 3x + -7x = 10 + 7x + -7x Combine like terms: 3x + -7x = -4x 50 + -4x = 10 + 7x + -7x Combine like terms: 7x + -7x = 0 50 + -4x = 10 + 0 50 + -4x = 10 Add '-50' to each side of the equation. 50 + -50 + -4x = 10 + -50 Combine like terms: 50 + -50 = 0 0 + -4x = 10 + -50 -4x = 10 + -50 Combine like terms: 10 + -50 = -40 -4x = -40 Divide each side by '-4'. x = 10 Simplifying x = 10
| 32+0.75o=47 | | 2/3x-5/9=3 | | 1/3=4-5x | | 6x-4=93+x | | 7+.2x=5+.3x | | m/4=.13 | | 11r^2-10r=-9 | | x+(30+36)=180 | | 99x=72 | | 2x+5=-3+9x | | 15+0.10(90-60)= | | 6+yi=x-6i | | 5x+7y=43 | | 5x^4+2x^3-x^2+4x+8=0 | | 14=6n | | 16x^4+20x^2-126= | | -5/2-5/6 | | (y-5)-(y+6)=7 | | 3x^2-2x+36=0 | | x+0.018=9 | | 7xy^6-6x^7=9y^8-7x-1 | | 7x-2-2x=3 | | x+4=15x-10 | | 5(x-1)=3(2x-7) | | e^5=10x | | 1/4(3x+2)-4/5(2x-3)=2/3(x-1) | | 4b+7a-8b= | | 2/3(4x-5)-1/2(3x+5)=3/4(x-2) | | 2/5-1/2x=9 | | -2(2)+4(-1)= | | 2/5-1/2=9 | | -3/4(x-2)=1/3(x-1) |